Rozumowanie przez analogie oparte na materiale geometrycznym u uczniów niewidomych - Kucharczyk, Izabella (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Analogical reasoning constitutes one of the ways the blind get to know the world; it enriches information and influences thinking. The purpose of the article is the presentation of results of research on reasoning using geometric analogies in blind pupils aged 10, 12 and 14. The study encompassed a group of 63 blind pupils and 63 seeing pupils. The study used the twelve series B matrices from the Progressive Matrices of John C. Raven. A detailed analysis of the dependencies between the variables permitted the determination of differences between groups of pupils in terms of reasoning using geometric analogies.